STRATEGI PROMOSI KESEHATAN UNIT MALARIA CENTER KABUPATEN HALMAHERA SELATAN - , Riskal Muslim, Prof. dr. Adi Utarini, M.Sc., MPH. P.hD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Malaria remains a public health problem. A total of 74% of districts in Indonesia have the status of endemic malaria, and although the case of yearover- year decline, but the numbers are still very large. South Halmahera had similar problems, including illustrated the extraordinary incident (outbreak) malaria occurring in a row with a high number of deaths and 71.4% of whom are children under five. Anticipation done through various ways one of which is the development of malaria center. Various activities have been implemented by the unit to suppress the development of malaria through health promotion approach. Interesting to study further insight into the presence, role and processes of health promotion model development. Objective: This study aimed to describe malaria centers in malaria prevention through the development of health promotion both in the scope of the policy, partnership and empowerment organization in the District of South Hamlahera. Method: The type of research is a qualitative study aimed to describe the role of malaria center in the development of health promotion malaria prevention in South Halmahera district. Key informant research is 2 Health Department officials, and 5 managers Malaria Center District and Provincial. While informants consisted of 5 officers support cross-sectoral, Head and malaria health center program managers by 5 people, Village Health Workers by 4, 5 village government officials, village cadres malaria as many as 3 people and 8 teachers of primary school teachers. Primary data were collected by in-depth interviews with stakeholders and program managers. Testing the validity of the data is done by triangilasi methods and sources, member checking and peer debriefing. Data analysis was performed concurrently with data collection (on going analysis). The process of data analysis includes interview transcription, coding and categories, interpretation of data and the subsequent conclusion. Results: advocacy activities generally conducted in a planned manner and in a team to produce some products that policy makers and local regulations or decree. these policies governing the duties and responsibilities of local government, cross-sector partnerships both at the district, sub-district and village, as well as the organization and functioning of the Malaria Center. In addition the policy also regulates the use of village funds allocation (VFA), which is the largest budget allocation of malaria control programs. Activities supportive environment and health promotion for this form: Socialization and campaigns through various media both print and electronic and health promotion with the use of technology that is Wibsite, SMS Center, and the Bulletin. Selian that health promotion is also done through the media in the room and outside the room such as posters, banners, leaflets, flipchar, banners and billboards and other-lian. Promotional activities that are eduakasi through formal learning in schools also developed the Local Content Curriculum Malaria, but its application is still in the 15 elementary schools. Strategy of community empowerment approach developed by Participatory Learning And Action (PLA) began in 2007-2010. Pattern empowerment PLA a joint training is participatory society. With the techniques and methods such as mapping Boddy, Timeline, Trand and Change, and venn diagram aims to increase public knowledge about the symptoms and causes of malaria, malaria prevention methods, identify potential resources in the village, make a plan of action with the community and mobilize the community to eradicate vectors. Conclusion: The success of health promotion strategies malaria advocacy center through a variety of approaches has spawned numerous products and establishment of regional kebiakan partnerships with various stakeholders to support the malaria control program. although not all are actively involved in cross-sectoral cooperation, so that needs to be improved coordination agenda. Health promotion activities and community empowerment that has been done has been able to increase the knowledge and participation of the community through vector eradication activities that are routine in the village. However, activity building efforts continue to be made periodically to maintain the continuity of community empowerment.